ISO 9001: 2008-Based School Management at SMP Negeri 3Purworejo - Iskhoriyah, Siti (2012)
The purpose of this thesis is to describe the planning, implementation, and follow-up of school based on ISO at SMP Negeri 3 Purworejo. It was a qualitative research by using ethnography design. The main subjects were the principal, teachers, and students. Data collection method used interview, observation, and field note. Data analysis technique used an interactive model of analysis. Data validity was tested by using credibility, transferability, confirmability, and dependability. The findings suggested that the planning of SMP Negeri 3 Purworejo to become ISO-based school is by holding cooperation with an international accreditation (consultant). Principal and consultant organized training for introducing and interpreting ISO-based school. Specialized personnel consisted of principal, Deputy Quality Management, teachers, administrative staffs and also the school board. These personnel made a submission proposal and also collected supporting document as the physical evident to the consultant. The proposal contains a map of the process, the condition of eight national standards, as well as targets to be achieved. The internal party of school and also consultant reviewed and completed the incomplete document. ISO-based school implementation at SMP Negeri 3 Purworejo was based on ISO standards school management. These standards were made in SOP module (standard operating procedure) that contained the work and task procedures. School management included foreign elements such as curriculum implemented by organizing the bilingual classes. The management of document is still manual, not using barcode system. Follow-up of ISO-based school in SMP Negeri 3 Purworejo is by holding the management review regularly. The activity was conducted by reviewing the application of quality management system which included the audit results, customer complaints, process performance and product conformity, status of corrective and preventive actions, recommendations and improvements. Each school activities are managed by the parties designated by the principal through the division of job description. All school personnel are required to document any educational activity does.